The impacts of gender-specific traumatic events on refugee women's psychological wellbeing - Melika Taheri; Sally Fitzpatrick; Lynne McCormack (Instituto Politécnico de Viseu, 2022)
Introduction: Forced migration, in general, comprises a series of traumatic events in a prolonged multiphase period; however, women refugees typically endure gender-specific traumatic events through their migration journey. Despite the typical reported negative impacts of traumatic events, the literature also identifies positive posttraumatic changes as posttrauma psychological wellbeing. Objective: To systematically identify the gender-based traumatic events throughout the migration journey and the impact of these events on the refugee women's posttrauma psychological wellbeing Methods: The PRISMA Extension for Scoping Reviews (Tricco et al. 2018) and the Joanna Briggs Institute Manual for Evidence Synthesis (Peters et al. 2020) will guide this scoping review. Therefore, it will systematically review academic and grey literature extracted from PsycInfo, PubMed, Embase, SCOPUS, CINAHL, as well as Open Grey and Google Scholar. The search strategy will consist of synonyms for the three basic constructs: gender-specific traumatic events, psychological wellbeing, and women refugees. Two reviewers will review and extract results from qualitative, quantitative, and mixed methods studies. The results will be coded and presented thematically using NVivo version 11. Results: The identified gender-based traumatic events throughout the migration journey and the impact of these events on the refugee women's posttrauma psychological wellbeing will be comprehensively presented in the full report. Conclusion: The findings will identify key concepts, the research gaps, and types and sources of evidence to understand refugee women's psychological wellbeing post-resettlement.